Phonetic Substitution and Its Enriching Function (Quranic Readings as a Model) - Nasser , Abdullah Jabr (Thi Qar Arts Journal, 2024)
AbstractThis study aims to demonstrate the impact of phonetic substitution between consonants or vowels in enriching the language with new terms, as it is a common phonetic phenomenon in all languages, including Arabic. Replacing one sound with another has its own features and characteristics, which undoubtedly leads to the emergence of new meanings unless the substitution is dialectal.Since the Quranic readings are an inexhaustible rich resource, the study found in them a fertile field to rely on in conveying the research idea.The study reached several conclusions, among the most prominent were: Phonetic substitution in consonants leads to a change in meaning, whether the substituted sounds are from the same point of articulation, like the sounds of “ض” and “ظ”, or from distant points of articulation, like the sounds of “ث” and “ب”. The short vowels vary in their heaviness, and the research revealed the precision of the Quranic text’s use of the vowel in its place, as in “وِقر” and “قَر”.